Islamic Biography Books and Their Significance in preserving Cultural and Scientific Heritage of Islam - Athamneh, Mohamed Saeed Salah (Journal of Humanities & Social Sciences, 2020)
This research aims to reveal the reality Islamic biography books and their Significance in preserving Cultural and Scientific Heritage of Islam. This research is based on the historical resources and references (most significantly، mental and literary books، as modern and late biography ones. Moreover، the study explains how biography books have contributed in the cultural، scientific and cultural development of the Arab Islamic nation via the earlier start of the Islamic culture; and the role of the Holy Quran and the Sunnah in its development and prosperity. Furthermore، the study highlights the development of writing biography books، the factors that distributed in its foundation، the efforts made by the scolars of biography books to highlight the civilizational، scientific and cultural image of the Islamic nation via the ages. As well as the Arab-Islamic civilization’s. Eventually، the research came with a conclusion that clarified the results of the study.